Immunomodulatory and anti-inflammatory therapeutic potential of gingerols and their nanoformulations - Çiğdem Yücel; Gökçe Şeker Karatoprak; Özlem Bahadır Açıkara; Esra Küpeli Akkol; Timur Hakan Barak; Eduardo Sobarzo-Sánchez; Eduardo Sobarzo-Sánchez; Michael Aschner; Samira Shirooie (Frontiers Media S.A., 2022)
Ginger (Zingiber officinale Roscoe), a member of the Zingiberaceae family, is one of the most popular spices worldwide, known since ancient times, and used both as a spice and a medicinal plant. The phenolic compounds found in ginger are predominantly gingerols, shogaols, and paradols. Gingerols are the major phenolic compounds found in fresh ginger and contain mainly 6-gingerol as well as 4-, 5-, 8-, 10-, and 12-gingerols. Gingerols possess a wide array of bioactivities, such as antioxidant and anticancer, among others. Regarding the different array of biological activities and published data on the mechanisms underlying its action, the complex interaction between three key events, including inflammation, oxidative stress, and immunity, appears to contribute to a plethora of pharmacological activities of this compound. Among these, the immunomodulatory properties of these compounds, which attract attention due to their effects on the immune system, have been the focus of many studies. Gingerols can alleviate inflammation given their ability to inhibit the activation of protein kinase B (Akt) and nuclear factor kappa B (NF-κB) signaling pathways, causing a decrease in proinflammatory and an increase in anti-inflammatory cytokines. However, given their low bioavailability, it is necessary to develop new and more effective strategies for treatment with gingerols. In order to overcome this problem, recent studies have addressed new drug delivery systems containing gingerols. In this review, the immunomodulatory activities of gingerol and its underlying mechanisms of action combined with the contributions of developed nanodrug delivery systems to this activity will be examined.